2021
DOI: 10.1007/s11250-021-02800-5
|View full text |Cite
|
Sign up to set email alerts
|

A viewpoint on the use of microalgae as an alternative feedstuff in the context of pig and poultry feeding—a special emphasis on tropical regions

Abstract: With the current increase in meat and animal products consumption, there is a need to make production systems more sustainable. The use of microalgae in monogastric feeds, replacing widely used conventional feedstuffs such corn and soybean, can be a solution to overcome this problem. Several studies have shown promising results in the use of microalgae in feeding of both pigs and poultry. However, there are several important constraints associated to the production of microalgae. Such constraints are particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Unlike traditional food crops, microalgae can grow in a variety of environments without requiring arable land, and, therefore, avoid competition with crops, such as soybean and cereal grains [ 4 ]. In addition, the ability of microalgae to fix carbon from the atmosphere makes them a valuable tool in reducing greenhouse gas emissions [ 5 ]. Therefore, the reasons for choosing microalgae as an ingredient or supplement for animal feed are, for instance, their high nutritional value, if cultured under optimal conditions and fed to adapted animals [ 6 ], and their ability to act as feed additives.…”
Section: Introduction Of Chlorella Vulgarismentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike traditional food crops, microalgae can grow in a variety of environments without requiring arable land, and, therefore, avoid competition with crops, such as soybean and cereal grains [ 4 ]. In addition, the ability of microalgae to fix carbon from the atmosphere makes them a valuable tool in reducing greenhouse gas emissions [ 5 ]. Therefore, the reasons for choosing microalgae as an ingredient or supplement for animal feed are, for instance, their high nutritional value, if cultured under optimal conditions and fed to adapted animals [ 6 ], and their ability to act as feed additives.…”
Section: Introduction Of Chlorella Vulgarismentioning
confidence: 99%
“…It can grow autotrophically, heterotrophically, or mixotrophically, and is usually cultured in raceway ponds or photobioreactors [ 11 ]. The nutritional composition of Chlorella is influenced by growing conditions and species, but it is a rich source of high-quality protein, minerals, vitamins, and pigments [ 5 ]. For example, Chlorella vulgaris (CV) can contain up to 67% dry matter (DM) of protein, with digestibility coefficients comparable to those of beans, oats, and wheat [ 12 , 13 ].…”
Section: Introduction Of Chlorella Vulgarismentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome such challenges, significant efforts have been conducted toward the development of alternative sustainable high-quality protein feed resources. These include for instance microalgae ( Chaves et al., 2021 ). The unicellular green microalga, Chlorella vulgaris, has a balanced essential amino acid profile ( Lamminen et al., 2019 ), being suitable as a protein source in feeds.…”
Section: Introductionmentioning
confidence: 99%
“… Bennato et al (2020) widely demonstrated, in lactating ruminants, the influence of diet on volatile profile of dairy products, both fresh and ripened. Other studies showed a significant modification in the fatty acid composition and sensory profile of the milk, while several trials reported no modification in the milk yield and in the animal performance ( Terramoccia et al, 2013 ; Mele et al, 2014 ; Cibik and Keles, 2016 ; Chaves et al, 2021 ) and the aromatic profile animal-derived food ( Caputo et al, 2015 ). Therefore, it is of paramount importance to in depth investigate the relationship between feeding management strategies and nutritional and nutraceutical properties of dairy products, in order to meet the current trend of consumer choices toward high-quality food ( Bonanno et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%